The influence of the guided discovery learning model on critical thinking ability and problem-solving ability - Irsyadah, Naeli; Dwiastuti, Sri; Indrowati, Meti (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2023)
This study aims to determine the effect of the guided discovery learning (GDL) model on critical thinking skills and problem-solving skills, the extent of the influence of the model on each aspect of critical thinking skills and aspects of problem-solving skills and look for the effectiveness of the model on critical thinking skills and problem-solving skills. The population in this study were all students of class X Mathematics and Natural Sciences. The sampling technique was purposive sampling. Research instrument with description test. The results showed that there was an influence of the model on critical thinking skills and problem-solving skills, the influence of the model on aspects of critical thinking skills from high to low are advanced clarification, inference, elementary clarification, strategies and tactics, basic support and aspects of problem-solving skills from high to low are define the problem, planning solutions, implement solutions, evaluate and check problems. The GDL model is effective for improving critical thinking skills and problem-solving skills.